Analysis Of The Calculation Of The Inheritance In The Family - Sriono, Sriono; Sri Dewi; Hendra Sony Rambe (Publisher Cv. Inara, 2020)
This research discusses about the calculation of the division of the inheritance against his polygamous wives. the method used in this research is using a normative juridical approach, namely by using the approach to laws and regulations applicable in Indonesia as well as the norms that live in society, data obtained from secondary data, namely the rules and regulations and the material of literature. Marriage polygamy is a marriage which one of it where men have or marry more than one womenor wife. Inheritance is an integral part of a marriage where the legal heirs are divided into two principles of marriage including monogamy and polygamous marriage. As for the calculation part of the legacy of the wives of a polygamous marriage calculated from the wealth obtained from each mating that they do. The division of property in a law of inheritance i.e., by observing the position of each wife. While the right part of the wife is shared jointly by the part of the wife such as ¼ if there are no children and 1/8 if there are children.